2019
DOI: 10.1097/md.0000000000017322
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of rehabilitation training combined acupuncture for the treatment of neurogenic bladder secondary to spinal cord injury

Abstract: Background:This study will aim to assess the effectiveness of the rehabilitation training (RT) combined acupuncture for the treatment of patients with neurogenic bladder (NB) secondary to the spinal cord injury (SCI).Methods:We will conduct a comprehensive literature search from the following databases from the inceptions to the present with no language limitation: PUBMED, EMBASE, Cochrane Library, SinoMed, Web of Science, Allied and Complementary Medicine Database, VIP, WANGFANG, Chinese Biomedical Literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Acupuncture is one of the therapies in traditional Chinese medicine. Clinical trials have shown that acupuncture can effectively treat a series of complications after SCI (Fan et al, 2018;Yang et al, 2019). A series of studies have shown that EA can improve locomotor function (Dai et al, 2019;Luo et al, 2019) and relieve neuropathic pain (Yan et al, 2019) after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is one of the therapies in traditional Chinese medicine. Clinical trials have shown that acupuncture can effectively treat a series of complications after SCI (Fan et al, 2018;Yang et al, 2019). A series of studies have shown that EA can improve locomotor function (Dai et al, 2019;Luo et al, 2019) and relieve neuropathic pain (Yan et al, 2019) after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…The specific power unit is shown in Figure 1 . Based on the requirements of this system, the STM32F103 microcontroller is adopted as the microcontroller of this project [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, further research on urinary retention after hysterectomy is needed. There are 2 [ 45 , 46 ] systematic reviews and meta-analysis on the treatment of neurogenic bladder with acupuncture after spinal cord injury. The sex of the patients includes male, and the nature of the injury is urinary retention caused by central nerve injury.…”
Section: Discussionmentioning
confidence: 99%